Resolution of the Expert Council “New approaches to the treatment of axial spondyloarthritis” - A. M. Lila; V. I. Mazurov; E. L. Nasonov; S. A. Lukyanov; T. V. Dubinina; I. Z. Gaidukova; A. A. Klimenko; S. A. Lapshina; G. V. Lukina; M. A. Korolev; R. O. Dreval; P. I. Pchelnikova; et al. (Современная ревматология)
On 30 May, 2024, an expert meeting was held to update the approaches for the treatment of axial spondyloarthritis (axSpA). A new approach to the treatment of axSpA was considered, which consists of depleting autoreactive TRBV9+ T- lymphocytes by introducing a monoclonal antibody – the drug seniprutug. The value of the drug seniprutug in the treatment of the disease was discussed and key aspects for the incorporation of the drug seniprutug into real-world clinical rheumatological practice were agreed.